2016
DOI: 10.3945/ajcn.115.129346
|View full text |Cite
|
Sign up to set email alerts
|

Effects of wheat-flour biscuits fortified with iron and EDTA, alone and in combination, on blood lead concentration, iron status, and cognition in children: a double-blind randomized controlled trial

Abstract: Food fortification with iron and EDTA additively reduces BPb concentrations. Our findings suggest that NaFeEDTA should be the iron fortificant of choice in lead-exposed populations. This trial was registered at clinicaltrials.gov as NCT01573013.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 40 publications
1
49
1
Order By: Relevance
“…daily amount of fortified MN, determined as the daily difference between the intervention and control group); and study results (details on extracted data in the study protocol: http://www.crd.york.ac.uk/prospero/). For six studies with more than two intervention groups and one control group [2429] we combined the intervention groups to create a single pairwise comparison (Cochrane Handbook; Chapter 16.5.4 [18]).…”
Section: Methodsmentioning
confidence: 99%
“…daily amount of fortified MN, determined as the daily difference between the intervention and control group); and study results (details on extracted data in the study protocol: http://www.crd.york.ac.uk/prospero/). For six studies with more than two intervention groups and one control group [2429] we combined the intervention groups to create a single pairwise comparison (Cochrane Handbook; Chapter 16.5.4 [18]).…”
Section: Methodsmentioning
confidence: 99%
“…It has been argued, however, that this ADI may have been set too low [56], and a recent trial in Moroccan children has shown that daily oral intake of EDTA can reduce blood lead concentrations [57], which is important in view of the enormous public health burden due to lead exposure in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Iron and Na2EDTA each independently resulted in modest but statistically significant reductions in children's BLLs. 20 The trials in Mexico and India enrolled children with similar BLLs (mean of 11.4 and 12.0 mg/dL, respectively), and Moroccan children had lower BLLs (adjusted geometric mean of 4.3 mg/dL). In contrast, 12% of the Mexican children,~70% of the Indian children, and 32% of Moroccan children had iron deficiency.…”
Section: Iron Status Intake and Supplementationmentioning
confidence: 99%
“…The recent RCT of iron fortification is a notable exception. 20 There is an implicit assumption that the recommendations are appropriate for children with low or very low lead exposure; this assumption needs to be tested further.…”
Section: Tempering Expectationsmentioning
confidence: 99%
See 1 more Smart Citation